Ultrathin Metallic NbS2 Nanosheets with Unusual Intercalation Mechanism for Ultra‐Stable Potassium‐Ion Storage. (11th June 2022) - Zhou, Jinhui; Shen, Yiheng; Lv, Fan; Zhang, Weiyu; Lin, Fangxu; Zhang, Wenshu; Wang, Kai; Luo, Heng; Wang, Qian; Yang, Huai; Guo, Shaojun
Abstract: Transition metal dichalcogenides (TMDs) show great potential as anodes for potassium‐ion batteries (PIBs) due to their high theoretical capacity and relatively low working potential. However, usually the conversion mechanism seriously hinders the long‐term cycle stability for PIBs due to the huge structural change. Herein, the synthesis of a class of ultrathin metallic 2H‐phase NbS2 nanosheets with large expanded interlayer spacing of 0.65 nm and high conductivity for boosting the potassium ion storage is reported. It is demonstrated that the as‐prepared NbS2 nanosheets show an unexpected intercalation mechanism for potassium ion storage, which is conceptually different from the well‐known intercalation‐conversion mechanism of typical TMDs. As a consequence, the ultrathin NbS2 nanosheets deliver superior rate capability (205.5 mAh g −1 at ultrahigh current density of 10 A g −1 ) and outstanding long‐term cycling performance (169.5 mAh g −1 at 5 A g −1 after 4000 cycles with a very low decay rate of 0.005% per cycle), representing the most stable TMD‐based anode materials for PIBs. Ex situ measurements and first‐principles calculations disclose and interpret that NbS2 nanosheets store potassium ions through only the intercalation mechanism without any conversion reaction taking place in the potassiation/depotassiation process, which highly improves the structural stability of electrode materials, hence promoting the long‐term cycle performance. Abstract : Ultrathin metallic NbS2 nanosheets with expanded interlayer spacing (0.65 nm) are applied as anodes for potassium ion batteries. An unexpected intercalation mechanism is discovered to be responsible for the storage of potassium ions, which is totally different from the intercalation‐conversion mechanism of most transition metal chalcogenides, significantly improving the structural stability of electrodes and promoting the long‐term cycle performance.